2017
DOI: 10.1016/j.expneurol.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuron subset-specific Pten deletion induces abnormal skeletal activity in mice

Abstract: Individuals with a history of epilepsy are at higher risk for bone fractures compared to the general population. Although clinical studies support an association between low bone mineral density (BMD) and anti-seizure medications, little is known on whether a history of seizures is linked to altered bone health. Therefore, in this study we tested the hypothesis that bone mass, morphology, and bone mineralization are altered by seizures in genetically epileptic animals and in animals subjected to an episode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Cite this article as Cold Spring Harb Perspect Med 2020;10:a037010 repetitive behavior, and self-grooming in the open field were decreased in one study (Lugo et al 2014), although increased stereotypy was also shown in 6-week-old males (Lugo et al 2017), and normal self-grooming was also observed (Smith et al 2016). No differences in this behavior were found in Pten Tg mice (Sanchez-Puelles et al 2019); decreased self-grooming and stereotypes were also found in L7-Cre; Pten loxP males (Cupolillo et al 2016).…”
Section: Behavior Of Mouse Models With Pten Mutationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Cite this article as Cold Spring Harb Perspect Med 2020;10:a037010 repetitive behavior, and self-grooming in the open field were decreased in one study (Lugo et al 2014), although increased stereotypy was also shown in 6-week-old males (Lugo et al 2017), and normal self-grooming was also observed (Smith et al 2016). No differences in this behavior were found in Pten Tg mice (Sanchez-Puelles et al 2019); decreased self-grooming and stereotypes were also found in L7-Cre; Pten loxP males (Cupolillo et al 2016).…”
Section: Behavior Of Mouse Models With Pten Mutationsmentioning
confidence: 92%
“…Only a small subset of conditional knockout models showed altered locomotor behavior, and even in these the results were inconsistent. Both the NS-Cre; Pten loxP and Nse-Cre; Pten loxP lines showed increases in distance traveled, although only when older than 6 weeks of age, and in the case of Nse-Cre; Pten loxP mice, only under stressful conditions (Kwon et al 2006;Zhou et al 2009;Lugo et al 2014Lugo et al , 2017. DAT-Cre; Pten loxP mice of unknown sex(es) showed normal open field activity, but males traveled a shorter distance than controls in the three-chamber test (Diaz-Ruiz et al 2009;Clipperton-Allen and Page 2014).…”
Section: Locomotionmentioning
confidence: 99%
“…PLEKHA1 is notably associated with the signaling pathway of PI3K/Akt, which plays an important role in osteoporosis [65,66]. Based on a mouse model, deletion of PtdIns (3,4,5)P 3 in the brain results in impaired bone mass and mineralization [67] and down-regulated PtdIns(3,4,5)P 3 levels also affected osteoclast activity and BMD [68]. PLEKHA1 can regulate PtdIns(3,4)P 2 and PtdIns (3,4,5)P 3 implying that PLEKHA1 might participate in bone metabolism through regulating PtdIns(3,4,5)P 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal model work demonstrates a direct effect of carbamazepine and phenytoin on voltagegated sodium channels within osteoblasts, 37 which may explain the observed reduction in bone density. 39 However further study is needed due to the number of genetic mutations associated with epilepsy/and epilepsy syndromes, with the relationship of these then in turn needing to be linked to bone phenotypes. Valproate has also been shown to increase bone resorption (based on bone turnover marker results), without impacting vitamin D metabolite levels.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, AED-independent mechanisms related specifically to the epilepsy state are also possible, with recent evidence that with a specific genetic murine model of epilepsy (the Pten knockout mouse), reduced bone mass accrual was seen in the absence of AED use. 39 However further study is needed due to the number of genetic mutations associated with epilepsy/and epilepsy syndromes, with the relationship of these then in turn needing to be linked to bone phenotypes. Overall, although these results are intriguing, the underlying mechanism for low bone mass in this population remains unclear.…”
Section: Discussionmentioning
confidence: 99%